DEVELOPMENT OF TECHNOLOGICAL COMPETENCIES OF TECHNOLOGICAL EDUCATION STUDENTS - Mukhitdinova Jamilakhon Ruslanovna; Goporova Shokhzoda To‘lqin qizi (Modern American Journals, 2025)
In the article there elucidated that in technology lessons, students are exposed to the existing structural elements in determining the components of technological thinking, which are the basis of developing and teaching students, and in addition, for the first time, four new components of technological thinking (thrift, affordability, diversification, critical analysis) were proposed, and as a result of their consideration, effective and it has been shown that they are important components in having a high-quality technological solution.
Keywords: Technique, technology, development, thinking, structure, organization, conceptuality, figurativeness, practical, operativeness, technical language, thriftiness, consumer requirements, critical analysis, garment technology, design.